Auditing and Performance of Micro Finance Institutions: A Case Study of Rukiga SACCO Kabale Branch. - Niwamanya, Sarah (Kabale University, 2024)
The study examined auditing and performance of Micro Finance Institutions a case study of Rukiga SACCO Kabale branch. The objectives of the study were; to identify internal audit systems used at Rukiga Micro Finance Institution, to discuss the ways and means of improving internal Audit Systems to improve performance in Micro Finance Institutions, and to examine the relationship between auditing and performance of Micro Finance Institutions. A descriptive research design was used and data was collected using interviews and questionnaires. The study results on the internal audit systems used at Rukiga Micro Finance Institution, the highest number of respondents mentioned compliance monitoring while the lowest number of respondents mentioned special investigations audit. The study findings on the ways and means of improving internal audit systems to improve performance in Micro Finance Institutions, the highest number of respondents mentioned reporting by drafting the audit report during the reporting phase while the least number of respondents mentioned ensuring that recommendations have been implemented. The study findings on the relationship between auditing and the performance of Micro Finance Institutions, the highest number of respondents mentioned that effective auditing helps identify and assess risks within MFIs, such as credit risk, operational risk, and compliance risk and the least number of respondents mentioned that auditing helps identify inefficiencies in the operations of MFIs, such as wasteful spending, fraud, or ineffective internal controls. The study recommended that there should be ensuring that all internal policies, procedures, and audit findings are well-documented and accessible to relevant staff and maintain an organized repository for audit-related documents to facilitate easy reference.